2004
DOI: 10.4049/jimmunol.172.3.1483
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polysaccharides Stimulate T Cells with No Preferential Vβ Usage and Promote Anergy, Resulting in Protection against Experimental Abscess Formation

Abstract: Zwitterionic polysaccharides (Zps) from pathogenic bacteria, such as Bacteroides fragilis, are virulence factors responsible for abscess formation associated with intra-abdominal sepsis. The underlying cellular mechanism for abscess formation requires T cell activation. Conversely, abscess formation can be prevented by prophylactic s.c. injection of purified Zps alone, a process also dependent on T cells. Hence, the modulatory role of T cells in abscess formation was investigated. We show that Zps interact dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
53
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 47 publications
2
53
0
3
Order By: Relevance
“…In the present study, the immune response to the carrier was found to determine the Ab response to the PS-moiety of this monovalent Pnc1-TT conjugate in young as well as adult mice. Zwitterionic properties of PPS of serotype 1 have been reported to induce T cell stimulation and subsequent apoptosis [46], but do not explain the low T cell responses obtained in neonatal mice, as the TT carrier and not the conjugate, was used for in vitro stimulation. We have previously found that in vitro stimulation of spleen cells with native PPS-1 induces neither proliferation nor cytokine secretion in Pnc1-TT immunized young or adult mice (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the immune response to the carrier was found to determine the Ab response to the PS-moiety of this monovalent Pnc1-TT conjugate in young as well as adult mice. Zwitterionic properties of PPS of serotype 1 have been reported to induce T cell stimulation and subsequent apoptosis [46], but do not explain the low T cell responses obtained in neonatal mice, as the TT carrier and not the conjugate, was used for in vitro stimulation. We have previously found that in vitro stimulation of spleen cells with native PPS-1 induces neither proliferation nor cytokine secretion in Pnc1-TT immunized young or adult mice (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Here, we show that rational chemical modification can be used to produce a glycoconjugate vaccine in which the PS Ag has acquired additional adjuvant properties. This work is based on previous findings showing that natural ZPS, such as PSA, activate T cells and APCs (7,8,12). Because this biological activity depends on the zwitterionic structure of this capsular PS (20)(21)(22), we generated a similar charge motif in a vaccine candidate PS by the chemical introduction of positive charges into the naturally anionic capsular PS of GBS (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Toll-like receptor 2 (TLR2) has been identified as the receptor implicated in the activation of APCs induced by PSA (11). Because PSA injected in a rat abscess model induces protection against the bacterium (12), the use of ZPS that combine Ag and adjuvant properties in the same molecule may represent a strategy for vaccine design. Moreover, a number of vaccine candidates consisting of protein Ag fused to synthetic lipopeptides targeting TLR2 have been proposed in the past.…”
mentioning
confidence: 99%
“…This complex has a zwitterion nature (Stingele et al 2004) and a critical involvement in abscess formation (Coyne et al 2000). B. fragilis can modulate its surface antigenicity (phase dependent) and it has at least eight distinct polysaccharides (PSA to PSH) (Krinos et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…B. fragilis can modulate its surface antigenicity (phase dependent) and it has at least eight distinct polysaccharides (PSA to PSH) (Krinos et al 2001). It is well documented that the CPC is involved in abscess formation (Stingele et al 2004). This capsule modulation (Krinus et al 2001) may be used as a strategy to help the bacteria evade the host immune system and at the same time to colonise the host.…”
mentioning
confidence: 99%